2014
DOI: 10.1212/01.wnl.0000438230.33223.bc
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging and clinical features in type II (late-onset) Alexander disease

Abstract: Objective: To describe the imaging and clinical features in type II (late-onset) Alexander disease (AxD). Methods:We retrospectively identified all cases of type II AxD evaluated at Mayo Clinic, Rochester from January 1996 to February 2012. Clinical and neuroimaging data abstracted from the record included age at onset of symptoms, age at diagnosis, first symptom, neurologic symptoms, physical/neurologic findings on examination, genetic testing and/or biopsy (if performed), and MRI findings.Results: Thirteen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 16 publications
(21 reference statements)
2
53
1
Order By: Relevance
“…Here, we report two patients with adult-onset AxD, who developed early and Cognitive decline and behavioural problems have generally not been highlighted as features of adult-onset AxD in large case series [1][2][3], although a Japanese study reported behavioural abnormalities and cognitive impairment in 2/12 patients [5]. Our two cases suggest that cognitive decline and behavioural disturbance may be prominent and early features of adult-onset AxD, and that…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Here, we report two patients with adult-onset AxD, who developed early and Cognitive decline and behavioural problems have generally not been highlighted as features of adult-onset AxD in large case series [1][2][3], although a Japanese study reported behavioural abnormalities and cognitive impairment in 2/12 patients [5]. Our two cases suggest that cognitive decline and behavioural disturbance may be prominent and early features of adult-onset AxD, and that…”
mentioning
confidence: 69%
“…An adult-onset form of the disease is being increasingly recognised, and presents commonly with progressive ataxia, bulbar and pyramidal features, and dysautonomia [1][2][3].…”
mentioning
confidence: 99%
“…On the other hand, types 2 and 3 show various symptoms such as muscle weakness, spastic paralysis, ataxia, a bulbar or pseudobulbar sign, and autonomic dysfunction, and it is difficult to suspect AxD solely based on clinical symptoms. The characteristic findings of brain MRI are signal abnormalities or atrophy of the medulla oblongata and/or cervical cord [5,6,7,8], reported as a tadpole appearance [7]. However, there is no quantitative standard for assessment of the findings, and it is typical for evaluation to be solely based on clinicians' visual impression.…”
Section: Introductionmentioning
confidence: 99%
“…Although diagnostic MRI criteria for infantile AD have been defined by van der van der Knaap et al [4], recent studies suggest that the radiologic presentation of AOAD significantly differs from infantile-onset cases [5,6]. AOAD cases appear to have less cerebral white matter involvement.…”
Section: Discussionmentioning
confidence: 99%